Fault Detection in Wind Turbine: A Systematic Literature Review. Issue 5 (October 2013) - Purarjomandlangrudi, Afrooz; Nourbakhsh, Ghavameddin; Esmalifalak, Mohammad; Tan, Andy
Wind power has become one of the popular renewable resources all over the world and is anticipated to occupy 12% of the total global electricity generation capacity by 2020. For the harsh environment that the wind turbine operates, fault diagnostic and condition monitoring are important for wind turbine safety and reliability. This paper employs a systematic literature review to report the most recent promotions in the wind turbine fault diagnostic, from 2005 to 2012. The frequent faults and failures in wind turbines are considered and different techniques which have been used by researchers are introduced, classified and discussed.